Career Adapt-Abilities Scale - Dual Career Form (CAAS-DC): psychometric properties and initial validation in high-school student-athletes - Ryba, T. V.; Zhang, C.-Q.; Huang, Z.; Aunola, K. (Health Psychology and Behavioral Medicine: An Open Access Journal, 2017)
Talented adolescent athletes attempting to sustain academic and vocational training alongside the increasing demands of their athletic career often encounter difficulties, including lower vocational readiness and the challenge of adapting to life after elite sport. Therefore, it is necessary to better understand the specific competencies that youth athletes can draw upon to successfully combine sport and education into a dual career pathway. Building on the existing Career Adapt-Abilities Scale [Savickas & Porfeli, (2012). Career adapt-abilities scale: Construction, reliability, and measurement equivalence across 13 countries. Journal of Vocational Behavior, 80(3), 661-673], we developed a Dual Career Form of the Career Adapt-Abilities Scale (CAAS-DC) for use with adolescent student-athletes. A sample of 391 Finnish-speaking athletes completed the CAAS-DC at the beginning of their freshman year in sport high school. Adequate factorial validity of the CAAS-DC and internal consistency reliabilities of its five subscales were demonstrated in both exploratory structural equation modeling and confirmatory factor analysis. The concurrent validity of the CAAS-DC was demonstrated by positive and significant associations with self-esteem, sport task values, school task values, and career construction; and negative associations with school and sport burnout. Finally, partial strong measurement invariance was also observed across males and females. The evidence from this study suggests that the CAAS-DC is a promising self-report inventory that can be used by researchers and applied practitioners to assess young athletes` self-regulation capacities in dual career pursuits.